Nursing interventions in preventing pressure injuries in acute inpatient care: a cross-sectional national study - Tarja Tervo-Heikkinen; Anniina Heikkilä; Marita Koivunen; Tiina Kortteisto; Jaana Peltokoski; Susanne Salmela; Merja Sankelo; Tuija Ylitörmänen; Kristiina Junttila (BMC, 2023)
Abstract Background Several nursing interventions for pressure injury prevention have been identified, including risk and skin status assessment. The aim of this study was to explore prevention of pressure injuries in Finnish acute inpatient care. The data were collected on pressure injury risk and skin status assessments, repositioning, the use of support surfaces, preventive skin care, malnutrition risk assessment, and nutritional care. Methods This multicentre, cross-sectional study was conducted in 16 acute care hospitals, excluding psychiatric care. Adult patients from inpatient care were recruited on the annual international Stop Pressure Ulcers Day in 2018 and 2019. Enrolment covered 6,160 participants in 503 units. Descriptive statistics were used to describe pressure injuries, risk assessments, and preventive nursing interventions. Cross tabulation, Pearson's chi-square and Fisher's exact tests were also used. Reporting follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Results In all, 30% of the participants had their pressure injury risk assessed during the care, and for 19% within 8 h after admission. The same time limit in risk assessment was fulfilled for 16% of the participants with a pressure injury, and 22% of the participants using a wheelchair or being bedridden. A skin status assessment within 8 h after admission was conducted for 30% of all participants, and for 29% of the participants with a pre-existing pressure injury, and for 38% of the participants using a wheelchair or being bedridden. The risk of malnutrition was screened in 20% of the participants. Preventive interventions were targeted to participants with a pressure injury instead of patients with a high-pressure injury risk. Conclusion This study adds evidence about pressure injury risk assessments and the implementation of preventive nursing interventions in Finnish acute care. Skin status and pressure injury risk assessments were irregularly conducted, and the outcome was not used by nurses to guide the implementation of preventive interventions. The results reveal the gaps in evidence-based nursing practice, which require further efforts to prevent pressure injuries. Improving the national focus on pressure injury prevention practice is critical for improving healthcare for our patients.